The Reality of the Application of the E-twinning Program during Distance Learning from the Point of View of the Students of Khawla Bint Al-Azwar School in light of the Corona Pandemic - Shifaa Mohammad Aldgheim (Deanship of Scientific Research (DSR), the University of Jordan, 2023)
Objectives: The study aimed to identify the reality of the application of the e-Twinning program from the point of view of students of Khawla Bint Al-Azwar School during distance learning in light of the Corona pandemic. Methods: To achieve the objectives of the study, the researcher used the descriptive approach, and a questionnaire was applied to a random sample of (30) students from Khawla Bint Al-Azwar School, arithmetic means were used to calculate the degree of application of the  e-Twinning program among students of Khawla Bint Al Azwar School. Results: The study reached the following results: The degree of application of the e-Twinning program for students of Khawla Bint Al Azwar School during distance learning in light of the Corona pandemic came to a high degree with an arithmetic mean (of 4.5). The degree of difficulties in applying the e-Twinning program was medium, with an arithmetic mean (of 3.5). Conclusions: In light of the findings of the study, the researcher recommended emphasizing the importance of applying for the e-Twinning program in teaching, and the need to build computerized educational programs based on the application of the e-Twinning program, as well as educating parents about the importance of the e-Twinning program and its impact on the teaching and learning process, and emphasizing the training of students and teachers on it.